Comparación de Dos Modelos de Pipetas de Inseminación Artificial en la Cateterización del Canal Cervical de la Oveja - Rodríguez Gavancho, Francisco (2017)
The aim of this study was to compare the depth of penetration of a dye into the cervical canal in sheep, simulating an insemination by using a traditional artificial insemination (AI) gun and one with a special design that has at the end an inflatable balloon that prevents reflux of dye. Eighty reproductive tracts of non-pregnant ewes were collected from the local slaughterhouse in Lima, Peru and randomly distributed for catheterization with one of the two AI guns, depositing 0.5 ml of methylene blue. The balloon of the second AI gun was inflated before depositing the die. Subsequently, the cervical canal was exposed and the depth of entry of the AI guns and the dye were measured considering the edge of the first cervical ring as zero (0). Both AI guns penetrated 19.9 ± 9.6. The die reached the same depth with the traditional gun and 60.0 ± 9.7 mm with the modified pipette (p<0.05). It is concluded that by using the modified pipette is possible to deposit a fluid more closely to the uterus.